1989
DOI: 10.1021/ma00197a046
|View full text |Cite
|
Sign up to set email alerts
|

Growth of polypropylene particles in heterogeneous Ziegler-Natta polymerization

Abstract: Nascent polypropylene particles prepared with S-TiCl3 catalyst systems have been examined by small-angle X-ray scattering, wide-angle X-ray diffraction, and electron microscopy. The catalyst crystallites which disperse at the initial stage of polymerization uniformly within the polymer particles retain their initial size during the course of polymerization. As the polymerization proceeds, the 0.2-0.35-jtm primary polymer particles become visible under an electron microscope, and their size increases in proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 2 publications
2
79
0
Order By: Relevance
“…More detailed information about particle morphology has been achieved by either transmission or scanning electron microscopy 15,21 and by the application of the high-resolution synchrotron-computed microtomography. 22 We shall differentiate between the particle morphology and the texture of particle surface observed either by optical or electron microscopy because it is difficult to judge the internal morphology of particles from the texture of their surfaces.…”
Section: Experimental Observations Of Particle Morphologymentioning
confidence: 99%
“…More detailed information about particle morphology has been achieved by either transmission or scanning electron microscopy 15,21 and by the application of the high-resolution synchrotron-computed microtomography. 22 We shall differentiate between the particle morphology and the texture of particle surface observed either by optical or electron microscopy because it is difficult to judge the internal morphology of particles from the texture of their surfaces.…”
Section: Experimental Observations Of Particle Morphologymentioning
confidence: 99%
“…Murry et al employed a simple method for preparation of dispersed catalysts particles by a milling procedure which enabled direct TEM observations of TiCl 3 -based catalysts 5) . Kakugo et al studied morphological changes of TiCl 3 -based catalysts during the olefin polymerization by TEM observations with stained samples [6][7][8] . These authors reported that original catalyst particles broke into small particles which were dispersed over the resulting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the effective diffusion coefficients for the two regimes are not equal. The MGM model was well supported by experimental evidence from electron microscope and TEM studies [16][17][18]. Primary polymer particles with 0.2-0.35 μm in diameter in nascent polypropylene particles were directly observed by TEM technique and in the core of the individual primary polymer particles one or sometimes two catalyst crystallites existed [17].…”
Section: Particle Model Of Polyethylenementioning
confidence: 62%
“…However, as an important deviation from the idealized MGM model, the primary polymer particles formed into a secondary polymer globule structure with a diameter of about 1 μm. These polymer globules could be observed from SEM photographs of the particle and might contain several tens of primary particles [17,18]. Martin and McKenna [6] also found that for a wide number of polyolefin particles, neighbouring primary particles could meld into larger agglomerates, probably caused by the softening or melting of the polymer phase under the real reactor temperature.…”
Section: Particle Model Of Polyethylenementioning
confidence: 99%